Numerical Solution of Fuzzy Fredholm Integral Equations of the Second Kind using Bernstein Polynomials - Altaie, Sarmad A (Al-Nahrain Journal of Science, 2018)
In this paper, a numerical method is given for solving fuzzy Fredholm integral equations of the second kind, by using Bernstein piecewise polynomial, whose coefficients determined through solving dual fuzzy linear system. Numerical examples are presented to illustrate the proposed method, whose calculations were implemented by using the Computer software MathCadV.14.